PENERAPAN SAFETY MANAGEMENT SYSTEM PADA LEMBAGA PENYELENGGARA PELAYANAN NAVIGASI PENERBANGAN INDONESIA - Fiyanzar, Adin Eka; Nusraningrum, Dewi; Arofat, Osman (JURNAL MANAJEMEN TRANSPORTASI & LOGISTIK, 2016)
This study aimed to analyze the effect of the implementation of Safety Management System (SMS) and the use of information system on the Flight Safety in the Indonesian Air Navigation Services Organization both partially and simultaneously. The research uses quantitative methods, and the data are analyzed using linear regression, simple correlation both partially and simultaneously and path analysis. The result shows; implementation of Safety Management System (X1) as measured by the Flight Safety (Y) has a positive and significant contribution on the level of Flight Safety.Â  The amount of the application contribution of Safety Management System that directly contributes to the Flight Safety is 35.4%, so the research hypothesis which states that the Safety Management System application directly impacts significantly on Aviation Safety is accepted; the use of Information Systems (X2) as measured by the Flight Safety (Y) has a positive and significant contribution on the level of Flight Safety. The use of information systems contributions that directly contributes to aviation safety is 38.4%, so the hypothesis which states that the use of information system directly affects significantly the flight safety is acceptable; the total effect of simultaneous application of Safety Management System (X1) and the use of Information Systems (X2) contribute significantly to the Flight Safety (Y) as much as 66.3%. The remaining 33.7% is the influence of the other factors such as refresher and development training for air navigation personnel, aviation navigation equipment renewal and observation flight